Phosphorous Distribution In Chipanga Coal Seam, Section 2a, Moatize Coal Mine - Rogério Sendela; Leonardo Xerinda; Andre Vilanculos; Anivaldo Chevane (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
Moatize Coal Mine is located in Tete Province, in centre of Mozambique. The deposit contains Gondwana allochthonous coals, and has a large amount of mudstone and siltstone banding. Phosphorus levels in the coal can be high which impacts the use of the coals in steel making where phosphorus is considered a contaminant. The Chipanga seam in the Moatize deposit shows considerable variability, vertically within the seam and laterally across the deposit. The data available from the exploration work indicates that the phosphorus is predominantly present as Apatite but the Crandallite minerals also are significant. The concentration of phosphorus varies with coal particle density with the highest phosphorus levels found for the mid density coal which also shows the highest likely levels of apatite or fluorapatite. Crandallite minerals show higher potential concentrations in the Lower density coal..